Condicionantes da criação e desenvolvimento do curso de Ciências Sociais da Faculdade de Filosofia Ciências, e Letras de Marília - Souza, Luana Silva de [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work intends to analyze the historical process of constitution of the Social Sciences of the Faculty of Philosophy and Marilia Sciences. For both we considered two processes of which we believe that this course is a result, first the process of expansion of higher education in the state of São Paulo (internalization) which occurred via Isolated community colleges (IIES) and had the Faculties of Science and Letters Philosophy (FFCL) a strong expression and, according institutionalization of Social Sciences in Brazilian universities that also fits into the process of implementation and expansion of universities in our country. For the development of this work took as its starting point the notion of scientific field and political field developed by Pierre Bourdieu, both with regard to the formation of Social Sciences in Brazil as the process of formation and expansion of higher education has as a reference development in São Paulo. The work was performed by literature on higher education in the state of São Paulo, on the formation of social sciences in the country and also through interviews Memory Project at the University Documentation and Memory Center of UNESP (CEDEM / UNESP) documentary research in the Historical Documentation Center and University of Marilia (CEDHUM) and the Collection of the City Council of the City Council of Marilia which houses copies of newspapers from Marilia, Marilia Mail and the Daily.

O presente trabalho tem a intenção de analisar o processo histórico de constituição do curso de Ciências Sociais da Faculdade de Filosofia e Ciências de Marília. Para tanto consideramos dois processos dos quais acreditamos que esse curso seja resultante: primeiro o processo de expansão do ensino superior no interior do Estado de São Paulo (interiorização) que se deu via Institutos Isolados de Ensino Superior (IIES) e que teve nas Faculdades de Filosofia Ciências e Letras (FFCL) uma forte expressão e, segundo institucionalização das Ciências Sociais nas universidades brasileiras que também se insere no processo de implantação e expansão das universidades em nosso país. Para o desenvolvimento desse trabalho tomamos como ponto de partida a noção de campo científico e campo político desenvolvido por Pierre Bourdieu, tanto no que diz respeito à formação das Ciências Sociais no Brasil como o processo de formação e expansão do ensino superior tendo como referencia seu desenvolvimento no Estado de São Paulo. O trabalho foi executado através da levantamento bibliográfico sobre o ensino superior no estado de São Paulo, sobre a formação da Ciências Sociais no país e ainda por meio de entrevistas do Projeto Memória da Universidade do Centro de Documentação e Memória da UNESP (CEDEM/UNESP), de pesquisa documental no Centro de Documentação Histórica e Universitária de Marília (CEDHUM) e no Acervo da Câmara Municipal do Vereadores da Cidade de Marília que abriga exemplares dos jornais Correio de Marília e o Diário de Marília.
Keywords: Universidade Estadual Paulista Júlio de Mesquita Filho Faculdade de Filosofia e Ciências História; Ciencias sociais - Estudo e ensino; Ensino superior; Education, Higher